Implementing Solution-Focused Brief Model of Group Career Counseling: Elevating Students' Career Aspirations - Setyorini, Dyah Wahyu; Rajbina, Faza Zahra Wulan; Muslihati, Muslihati; Jannah, Fitriana Na’imatu; Hanafi, Husni (Proceedings Series of Educational Studies, 2024)
Career aspirations can be defined as a strong and directed desire to achieve success in the future. However, limited information and access to career opportunities often lead to confusion among students in planning their future career choices. Additionally, the tendency of students to choose further studies based on non-rational factors also contributes to this issue, necessitating appropriate interventions. This study aims to examine how students' career aspirations can be elevated through the intervention of group counseling using the Solution-Focused Brief Counseling (SFBC) approach. This quantitative study using quasi-experimental method with one-group pretest-posttest design. Data were collected using the "Career Aspiration Scale – Revised" (CAS-R). The sample consisted of 10 eleventh-grade students from UM Laboratory High School. Descriptive results indicated a significant difference in pretest and posttest scores. Further analysis using a paired t-test showed a positive significant difference in students' career aspiration scores before and after the intervention. The findings of this study suggest an increase in students' career aspirations following the implementation of group counseling with the Solution-Focused Brief Counseling approach. The practical implications of this study highlight the use of SFBC as a proven alternative to enhance students' career aspirations. Keywords: career aspiration; career counseling; career service; group counseling; sfbc;